Exploring Emotions Related to the COVID-19 Pandemic through Death Education: A Qualitative Study at Italian Primary Schools - Ines Testoni; Lorenza Palazzo; Erika Iacona; Ottavia Segalla; Laura Pizzolato; Matteo Rigo; Lea Ferrari (MDPI AG, 2023)
Background: The COVID-19 pandemic has impacted the lives of individuals, families, and children worldwide. In Italy, the implementation of measures such as lockdowns and distance learning in schools affected the mental health of children and families. Methods: This article employs a qualitative method to explore the efficacy of a death education project that aimed to help primary school children process the emotions and losses that they experienced during the COVID-19 pandemic. The study encompassed both the children who took part in the death education project and their teachers and parents to investigate their perspectives on the emotions of the minors and the effectiveness of the project. Results: Distance learning posed challenges for the learning process and exacerbated social inequalities. The children suffered from limited social contact with their friends and experienced negative emotions, including anger, fear, and concern for the health of their loved ones. The death education project provided a safe space for children's emotional expression and facilitated their acquisition of coping strategies. Open communication between adults and children about illness and death proved effective in mitigating the psychological impacts of loss and preventing traumatic bereavement. Conclusion: The findings highlight the utility of death education in enhancing children's ability to express their emotions and approach the topic of death more frankly.